Characterization of Synovial Cytokine Patterns in Bucket-Handle and Posterior Horn Meniscal Tears - Marco Turati; Davide Maggioni; Nicolò Zanchi; Marta Gandolla; Massimo Gorla; Paola Sacerdote; Silvia Franchi; Laura Rizzi; Alessandra Pedrocchi; Robert J. Omeljaniuk; Giovanni Zatti; Antonio Torsello; et al. (Mediators of Inflammation)
The specific etiology of meniscal tears, including the mechanism of lesion, location, and orientation, is considered for its contribution to subsequent joint cytokine responsiveness, healing outcomes, and by extension, appropriate lesion-specific surgical remediation. Meniscal repair is desirable to reduce the probability of development of posttraumatic osteoarthritis (PTOA) which is strongly influenced by the coordinate generation of pro- and anti-inflammatory cytokines by the injured cartilage. We now present biochemical data on variation in cytokine levels arising from two particular meniscal tears: bucket-handle (BH) and posterior horn (PH) isolated meniscal tears. We selected these two groups due to the different clinical presentations. We measured the concentrations of TNF-α, IL-1β, IL-6, IL-8, and IL-10 in knee synovial fluid of 45 patients with isolated meniscal lesions (BH tear, n=12; PH tear, n=33). TNF-α levels were significantly (p<0.05) greater in the BH group compared with the PH group, whereas IL-1β levels were significantly greater (p<0.05) in the PH group compared with the BH group. Both BH and PH groups were consistent in presenting a positive correlation between concentrations of IL-6 and IL-1β. A fundamental difference in IL-10 responsiveness between the two groups was noted; specifically, levels of IL-10 were positively correlated with IL-6 in the BH group, whereas in the PH group, levels of IL-10 were positively correlated with IL-1β. Collectively, our data suggest a possible influence of the meniscal tear pattern to the articular cytokine responsiveness. This differential expression of inflammatory cytokines may influence the risk of developing PTOA in the long term.